2021
DOI: 10.1021/acsmedchemlett.1c00046
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Surfactins as Inhibitors of MicroRNA Processing Using Cat-ELCCA

Abstract: MicroRNAs (miRNAs) are a family of small noncoding RNAs that regulate gene expression. Due to their important activity in the fine-tuning of protein translation, abnormal expression of miRNAs has been linked to many human diseases, making the targeting of miRNAs attractive as a novel therapeutic strategy. Accordingly, researchers have been heavily engaged in the discovery of small molecule modulators of miRNAs. With an interest in the identification of new chemical space for targeting miRNAs, we developed a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
5
9
0
Order By: Relevance
“…The HMBC signals from the α -proton and amide proton of each amino acid to the carbonyl carbon of the adjacent amino acid or β -OH acid and the NOESY correlations between the α -proton and amide proton of amino acids established the sequence of 1 as (cyclo-( β -OH acid-Glu-Leu-1-Leu-2-Leu-3)) ( Figure 2 ). The β -OH acid chain was estimated to be a linear type due to the remaining one methyl signal ( δ C 14.5 and δ H 0.89), which matched well with recently reported chemical shifts for the terminal methyl signal ( δ C 14.4 and δ H 0.90) of a linear β -OH acid [ 19 ].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The HMBC signals from the α -proton and amide proton of each amino acid to the carbonyl carbon of the adjacent amino acid or β -OH acid and the NOESY correlations between the α -proton and amide proton of amino acids established the sequence of 1 as (cyclo-( β -OH acid-Glu-Leu-1-Leu-2-Leu-3)) ( Figure 2 ). The β -OH acid chain was estimated to be a linear type due to the remaining one methyl signal ( δ C 14.5 and δ H 0.89), which matched well with recently reported chemical shifts for the terminal methyl signal ( δ C 14.4 and δ H 0.90) of a linear β -OH acid [ 19 ].…”
Section: Resultssupporting
confidence: 87%
“…However, by the detailed analysis of 2D NMR data, we found that the HDTA unit in 5 is a mixture of a 3-hydroxy-12-methyltetradecanoic acid and a 3-hydroxy-13-methyltetradecanoic acid, which have the same molecular weight and formula to HDTA, as shown in Figure 5 . This fact was also supported by the chemical shifts of the methyl signals ( δ C 19.8/ δ H 0.86, δ C 11.9/ δ H 0.87, and δ C 23.1/ δ H 0.87) of the β -OH acid in 5 , which were well matched with the literature values for the anteiso- and iso-type β -OH acids [ 19 ]. Therefore, the planar structures of 4 and 5 should be revised to have the same planar core structure as baciloterins C–E ( 1 – 3 ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Using our developed technique, we isolated over 1400 culturable antibiotic-producing isolates from soil, aquatic, and marine environments as part of the Tiny Earth TM Program [ 31 ]. More importantly, we coupled our culture technique with a data-based chemical analysis [ 32 , 33 ], leading to the identification of a new macrocyclic polyketide class of antibiotic, desertomycin H ( 2 ), together with the known congener desertomycin A ( 1 ). Structure elucidation of the metabolites was performed based on detailed spectroscopic analysis.…”
Section: Introductionmentioning
confidence: 99%